한반도 문제의 해결방법에 관한 제도주의적 접근 - 김학성; Hak Sung Kim (한국과 국제정치, 2016)
지금까지 한국 대북·통일정책의 소박한 성과에서 보듯이, 행위이론에 의존하는 기존의 접근방법으로는 구조적 복합성을 띠는 한반도문제를 해결하는 데 한계를 가질 수밖에 없다. 이를 감안하여, 본 논문은 행위와 구조의 상관성에 주목하는 제도주의를 기반으로 한반도 문제의 분석과 해결책을 모색하고자 한다. 따라서 일차적으로 신제도주의 이론을 한반도 문제에 적용하는 것이 얼마나 유용할 수있는지 보여주고자 한다. 이어서 한반도 문제의 구조 및 해결과제들을 신제도주의적 시각으로 설명 또는 재해석하고, 이를 기반으로 제도주의적 분석모델을 제시한다. 이 모델은 향후 한반도 문제해결과 관련된 연구나 정책대안의 모색과정에서 종합적인 판단기준을 제공할 수 있을 것이다. The usual approaches to the Korean Question, which cling to the methodology of action theory, seem to be inadequate to explain and solve the Korean Question with structural complexity clearly. This may be confirmed by the poor achievements in our policy toward North Korea as well as unification policy. Consequently it should be necessary to attempt to analyze and solve the Korean Question on the basis of the institutionalism which pays attention to the relationship between action and structure. In this context the first part of this paper focuses on the question, how much practical the application of the new institutionalism to the Korean Question could be. Thereafter it tries to explain and analyze the structure of the Korean Question and its solving tasks, and introduce in conclusion an institutionalist analytic model. This model would offer synthetic yardstick for judgement in the studies and searching for policy alternatives to analyze and solve the Korean Question.